Further investigations into the nature of phrasal compounding - Kornfilt, Jaklin; Trips, Carola (Morphological Investigations, 2017)
This collection of papers on phrasal compounding is part of a bigger project whose aims are twofold: First, it seeks to broaden the typological perspective by providing data for as many different languages as possible to gain a better understanding of the phenomenon itself. Second, based on these data which clearly show interaction between syntax and morphology it aims to discuss theoretical models which deal with this kind of interaction in different ways. Models like Generative Grammar assume components of grammar and a clear-cut distinction between the lexicon (often including morphology) and grammar. Other models, like construction grammar, do not assume such components and are rather based on a lexicon including constructs. A comparison of these models on the basis of this phenomenon on the morphology-syntax interface makes it possible to assess their descriptive and explanatory power.